2007
DOI: 10.1111/j.1460-9568.2007.05736.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress‐induced phosphorylation, degradation and aggregation of α‐synuclein are linked to upregulated CK2 and cathepsin D

Abstract: Intracellular accumulation of alpha-synuclein (alpha-Syn) as filamentous aggregates is a pathological feature shared by Parkinson's disease, dementia with Lewy bodies and multiple system atrophy, referred to as synucleinopathies. To understand the mechanisms underlying alpha-Syn aggregation, we established a tetracycline-off inducible transfectant (3D5) of neuronal lineage overexpressing human wild-type alpha-Syn. Alpha-Syn aggregation was initiated by exposure of 3D5 cells to FeCl2. The exposure led to format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 37 publications
6
100
1
Order By: Relevance
“…However, it remains unclear, how, when and where the CK2 kinase activity is regulated in cells (Miyata, 2009). Changes in CK2 activity induced by various stimuli are correlated with its protein levels (Takahashi et al, 2007). CK2 is normally expressed at a higher level than the catalytic subunits ( and Ј) of CK2, allowing some CK2 to be incorporated into tetramers and stabilized, whereas the excess CK2 is rapidly degraded with a half-life of less than 1 hour (Luscher and Litchfield, 1994).…”
Section: Ck2 Is a Regulator Of Hdac6 Catalytic Activity And A Bridge mentioning
confidence: 99%
“…However, it remains unclear, how, when and where the CK2 kinase activity is regulated in cells (Miyata, 2009). Changes in CK2 activity induced by various stimuli are correlated with its protein levels (Takahashi et al, 2007). CK2 is normally expressed at a higher level than the catalytic subunits ( and Ј) of CK2, allowing some CK2 to be incorporated into tetramers and stabilized, whereas the excess CK2 is rapidly degraded with a half-life of less than 1 hour (Luscher and Litchfield, 1994).…”
Section: Ck2 Is a Regulator Of Hdac6 Catalytic Activity And A Bridge mentioning
confidence: 99%
“…General protein degradation and turnover Many (including ↓) [36] Activation and degradation of polypeptide hormones, FGF [37] chemokines, growth factors and their receptors Plasminogen [38] Prolactin [39,40] Endostatin [41] Osteocalcin [42] Thyroglobulin [43] Insulin [44] Glucagon [45] IL-1 [46] IGFBP [47] Androgen receptor [48] Parathyroid hormone [49] MIP-1 alpha [50] MIP-1 beta [50] SLC [50] Activation of enzymatic precursors Cathepsin B [51,52] Cathepsin L [51,53] Transglutaminase 1 [54] Brain antigen processing Amyloid beta A4 protein [55,56] Tau [57] Tubulin [58] Myelin basic protein [59] Mhtt [60] Apolipoprotein E [61] Alpha-synuclein [62] Degradation of cytoskeletal proteins Neurofilaments [63] Actin [64,65] Myosin [64,66] Tropomyosin [65] Monocyte-mediated fibrinolysis Fibrinogen [67,68] Fibrin [67,68] Regulation of apoptosis Bid [69] Thiredoxin-1 [70] Processing of enzyme activators and inhibitors Prosaposin …”
Section: Biological Function Target Protein Referencementioning
confidence: 99%
“…CK1 has been found to co-localize with pS87 in transgenic mice and in LB-like structures in LBD/PD-diseased brains [75,76], and phosphorylates α-Syn at serine87 as well [26]. Oxidative stress induced by iron is reported to upregulate CK2 that leads to increased phosphorylated α-Syn serine129 with an associated increase in oligomerization and inclusion formation [65]. Smith et al [66] have shown in SH-SY5Ycells that the increase in α-Syn phosphorylation under oxidative stress is mediated by CK2 and correlates with enhancement of inclusion formation.…”
Section: Kinases Involved In α-Synuclein Phosphorylationmentioning
confidence: 99%
“…Serine129 of α-Syn can be phosphorylated by G protein-coupled receptor kinases (GRK1, GRK2, GRK5, and GRK6) [61][62][63], casein kinases 1 and 2 (CK1 and CK2) [26,[64][65][66][67][68][69], and the polo-like kinases (PLKs) [70]. Current studies have shown that, GRKs may also phosphorylate non-receptor substrates, comprising the four members of the Syn family (α-,β-,γ-Syn, and synoretin) in addition to phosphorylating agonist-occupied G protein-coupled receptors (GPCRs) [62].…”
Section: Kinases Involved In α-Synuclein Phosphorylationmentioning
confidence: 99%